Răspunsuri

2014-11-19T01:01:33+02:00
=4radikal din 9*10- radikal din 10-(3radikal din 16*10-5radikal din 10*4)=12radikal din 10-radikal din 10-(12radikal din 10-10 radikal din 10)=12radikal din10-radikal din 10-2radikal din10=9radikal din 10

2014-11-19T01:07:29+02:00
4 \sqrt{90} -\sqrt{10}-(3\sqrt{160}-5\sqrt{40})=
=4*3\sqrt{10}-\sqrt{10}-(3*4\sqrt{10}-5*2\sqrt10)=
=12\sqrt{10}-\sqrt{10}-(12\sqrt{10}-10\sqrt{10}=
=11\sqrt{10}-2\sqrt{10}=
=9\sqrt{10}
4radikal din 9*10- radikal din 10-(3radikal din 16*10-5radikal din 10*4)=12radikal din 10-radikal din 10-(12radikal din 10-10 radikal din 10)=12radikal din10-radikal din 10-2radikal din10=9radikal din 10
sper ca te-am ajutat
Am scris deja raspunsul